2020
DOI: 10.1097/ccm.0000000000004787
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training With an Electronic Resistive Loading Device Improves Prolonged Weaning Outcomes in a Randomized Controlled Trial*

Abstract: OBJECTIVES: To test if the use of an inspiratory muscle training program with an electronic resistive loading device is associated with benefits as to muscle strength, weaning, and survival in the ICU. DESIGN: Prospective randomized controlled trial. SETTINGS: Study conducted at the ICU of a Navy’s hospital, Rio de Janeiro, Brazil, from January 2016 to September 2018. PATIEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
0
24
1
Order By: Relevance
“…However, despite improvement in maximal inspiratory pressures, TTDN did not result in improved clinical outcomes. In previous studies, inspiratory muscle training increased both MIP and the proportion of weaned patients compared to control (31). A possible explanation for this difference, compared to our study, is that TTDN might not have yielded sufficient MIP improvement to result in statistically improved clinical outcomes in this under-powered study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, despite improvement in maximal inspiratory pressures, TTDN did not result in improved clinical outcomes. In previous studies, inspiratory muscle training increased both MIP and the proportion of weaned patients compared to control (31). A possible explanation for this difference, compared to our study, is that TTDN might not have yielded sufficient MIP improvement to result in statistically improved clinical outcomes in this under-powered study.…”
Section: Discussioncontrasting
confidence: 81%
“…Several other studies suggest that this is also the case for inspiratory muscle training (14,(29)(30)(31). However, inspiratory muscle training is difficult to generalize because it involves patient cooperation and requires time intensive physiotherapy resources that may not be systematically available.…”
Section: Discussionmentioning
confidence: 96%
“…da Silva Guimaraes et al 17 added to this body of literature through the use of a nontraditional threshold device, an electronic loading device. The purpose of this electronic loading was to better match the length tension curve of a muscle.…”
Section: Inspiratory Muscle Strength Trainingmentioning
confidence: 99%
“…17 Each exercise session consisted of 2 bouts of 3 sets of resistance breaths starting at 40% of target load with progression to 100% of target load with each set followed by 2 to 3 minutes of recovery. 17 The results of the study showed that IMST resulted in a higher survival rate and cumulative weaning success compared with the control group at 60 days. 17 In addition, both IMST and duration of ventilation showed significance for contributing to changes in successful weaning from MV.…”
Section: Inspiratory Muscle Strength Trainingmentioning
confidence: 99%
“…Daily inspiratory muscle training (IMT) with six to eight contractions repeated in three to four sets at moderate-to-high intensity has been shown to be safe and to improve both inspiratory muscle strength and weaning success in patients with difficulties weaning. 138,139 The studies performed so far on IMT in MV patients have been heterogeneous with regard to inclusion criteria, training modalities and outcomes evaluated. In addition, most of the studies used a mechanical threshold-loading (MTL) IMT device (►Fig.…”
Section: Weaning From Mechanical Ventilationmentioning
confidence: 99%